2014
DOI: 10.4238/2014.february.20.5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of evodiamine on expressions of lipogenesis and lipolysis genes in mouse adipose and liver tissues

Abstract: ABSTRACT. Evodiamine, the major alkaloid component isolated from the fruit of dried, unripened Evodia rutaecarpa Bentham, affects the plasma levels of cholecystokinin and various biological events such as gastric emptying and gastrointestinal transit; these effects of evodiamine were previously investigated in male rats. In this study, we aimed to investigate the effects of evodiamine on average daily weight gain, rectal temperature, and expressions of genes involved in lipid metabolism in liver and adipose ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Evodiamine is a naturally indoloquinazoline alkaloid isolated from Evodia rutaecarpa , attracting close attentions with its anti-cancer, anti-inflammation, and anti-obesity effects [ 13 17 ]. Many researches have indicated that both of berberine and evodiamine exerted on regulation of lipid metabolism [ 18 , 25 ], but whether they have a synergistic effect on preventing hyperlipidemia when combined together remains completely unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Evodiamine is a naturally indoloquinazoline alkaloid isolated from Evodia rutaecarpa , attracting close attentions with its anti-cancer, anti-inflammation, and anti-obesity effects [ 13 17 ]. Many researches have indicated that both of berberine and evodiamine exerted on regulation of lipid metabolism [ 18 , 25 ], but whether they have a synergistic effect on preventing hyperlipidemia when combined together remains completely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine was conformed to possess obvious cholesterol-lowering effect on serum TC, LDL-C, or non HDL cholesterol (non HDL-C) in plenty of researches [ 12 , 27 29 ]. Evodiamine was reported to have effect on lipid metabolism by regulation the key genes in fat synthesis [ 18 ]. The reductions of liver cholesterol might be a result of decreased cholesterol input arise from the inhibition of intestinal cholesterol absorption [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evodiamine (Evo), an indolequinone alkaloid that occurs naturally, is one of the primary bioactive components of medicinal plants including plant extracts of Evodia rutaecarpa, Evodiae fructus , and Euonymus europaeus . [ 1 ] Evo has gained increasing attention for its potentially beneficial pharmacological applications including anti‐tumor, [ 2 ] anti‐inflammatory, [ 3 ] anti‐bacterial, [ 4 ] anti‐neurodegenerative, [ 5 ] anti‐obesity, [ 6 ] anti‐depressant, [ 7 ] and cardiac protective. [ 8 ] Reported evidence suggested that Evo has anticancer properties in vivo and in vitro by inducing apoptosis, inhibiting proliferation, invasion, and migration of various cancer cell lines including cervical cancer cell line (i.e., HeLa cells).…”
Section: Introductionmentioning
confidence: 99%